2016
DOI: 10.1155/2016/1215746
|View full text |Cite
|
Sign up to set email alerts
|

Constipation and Laxative Use among Nursing Home Patients: Prevalence and Associations Derived from the Residents Assessment Instrument for Long-Term Care Facilities (interRAI LTCF)

Abstract: Introduction. Constipation is a common, bothersome, and potentially dangerous condition among nursing home (NH) patients. Between 50 and 74% of NH patients use laxatives. Objective. To study prevalence and associations of laxative use and constipation using the comprehensive Norwegian version of the Resident Assessment Instrument for Long-Term Care Facilities. Methods. Cross-sectional study. Patients from 20 NH units were included. Logistic regression was used to analyze the results. Data collected in NHs migh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 54 publications
3
17
0
1
Order By: Relevance
“…After 3 days without a bowel movement, a rectal exam should be conducted followed by a tap water enema. A combination of osmotic laxatives with stimulant or prokinetic laxatives (bisacodyl/senna or prucalopride) is also considered to be effective in nursing home residents suffering with constipation . A technical aid in the management of constipation that has been shown to have some effect in older people is an abdominal massage, which can increase the frequency of bowel movements and decrease discomfort in patients with constipation …”
Section: Discussionmentioning
confidence: 99%
“…After 3 days without a bowel movement, a rectal exam should be conducted followed by a tap water enema. A combination of osmotic laxatives with stimulant or prokinetic laxatives (bisacodyl/senna or prucalopride) is also considered to be effective in nursing home residents suffering with constipation . A technical aid in the management of constipation that has been shown to have some effect in older people is an abdominal massage, which can increase the frequency of bowel movements and decrease discomfort in patients with constipation …”
Section: Discussionmentioning
confidence: 99%
“…Autonomic dysfunction in PD, including sleep disorders, orthostatic hypotension, urinary dysfunction and constipation, often begins before motor symptoms and greatly impacts patients quality of life [37]. Constipation is especially common, occurring in 80–90% of PD cases, and is typically identified by patient reports of fewer than three bowel movements per week and hard stools [8,9]. Current anti-parkinsonian dopamine replacement therapies are not effective and can worsen gastrointestinal (GI) dysfunction [10].…”
Section: Introductionmentioning
confidence: 99%
“…Out of these, BSF types 1 and 2, time spent for defecation of more than 10 min, and abdominal bloating were independent predictors for the older people reporting chronic constipation. In previous studies, the prevalence of chronic constipation was higher among older people in Western countries 5,[16][17][18] than in Asia (21% to 75% vs. 16.5% to 25.8%). 4,9,19,20 Previous studies suggested that a high prevalence was probably due to the study population consisting of high-risk populations, such as nursing home residents 16,21 and women, 5 and the use of self-reporting or questionnaires.…”
Section: Discussionmentioning
confidence: 78%